2016
DOI: 10.1161/hypertensionaha.115.06071
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Treatment Ameliorates the Maternal Syndrome of Preeclampsia and Rescues Fetal Growth in the Dahl Salt–Sensitive Rat

Abstract: Preeclampsia, a hypertensive disorder of pregnancy, is detrimental to both mother and fetus. There is currently no effective treatment, but sildenafil, a phosphodiesterase-5 inhibitor, has been proposed as a potential therapy to reduce blood pressure and improve utero-placental perfusion in preeclamptic patients. We hypothesized that sildenafil would improve the maternal syndrome and fetal outcomes in the Dahl S rat model of superimposed preeclampsia. Dahl S rats were mated, and half received sildenafil (50 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 29 publications
(42 reference statements)
7
31
1
1
Order By: Relevance
“…Several groups have also reported that sildenafil may be beneficial in other animal models of pregnancy complications, such as the rat model of placental ischemia, the Dahl salt-sensitive hypertensive rat, and the catechol-O-methyltransferase-deficient model of growth restriction (31,33,40). Bolnick et al have also reported that trophoblast invasion, a process that is defective in preeclampsia, may be promoted by sildenafil in culture studies (41).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have also reported that sildenafil may be beneficial in other animal models of pregnancy complications, such as the rat model of placental ischemia, the Dahl salt-sensitive hypertensive rat, and the catechol-O-methyltransferase-deficient model of growth restriction (31,33,40). Bolnick et al have also reported that trophoblast invasion, a process that is defective in preeclampsia, may be promoted by sildenafil in culture studies (41).…”
Section: Discussionmentioning
confidence: 99%
“…74 Sildenafil improved maternal and fetal outcomes and reduced oxidative stress and ET-1 in models of experimental preeclampsia. 28,75 Release of Ca 2+ from intracellular stores and entry of Ca 2+ from the extracellular space cause an increase in intracellular Ca 2+ concentrations, which trigger the contraction of vascular smooth muscle. 76 Incubation of human umbilical smooth muscle cells cocultured with umbilical endothelial cells with serum from women with preeclampsia increased intracellular Ca 2+ concentrations and PKC-α (second messenger) activation.…”
Section: Angiotensin IImentioning
confidence: 99%
“…Interleukin-6 (IL-6) was increased in both non-pregnant and pregnant mice exposed to Br 2 . These cytokines have been shown to be associated with the onset of preeclampsia 12, 1924 . Tadalafil therapy subsequently reduced these levels to those similar to air controls (Figure 5A–C).…”
Section: Resultsmentioning
confidence: 99%